Intention To Pursue An Academic Career Among Malaysian University Students: The Role Of Passion, Role Model, Perceived Workplace Flexibility, And Career Decision-Making Self-Efficacy - Dasan, Jakaria (2017)
This research is timely to support Malaysia's aspiration to become a respected higher education hub in the` region where a sufficient number of academics have to be ensured. This can be determined by detecting the presence of certain features in a person to pursue an academic career. Most researches have attributed passion, role model, and workplace flexibility separately as influencing the intention to pursue an academic career. However, this study revealed interesting results when these factors are tested simultaneously. Four hundred and sixty three questionnaires were successfully analysed in a quantitative study involving four public universities which are known as the comprehensive university.